Inflammatory myopathy with anti-signal recognition particle antibodies: case series of 100 patients - Suzuki, Shigeaki (Orphanet J Rare Dis, 2015)
BACKGROUND: Anti-signal recognition particle (SRP) antibodies are used as serological markers of necrotizing myopathy, which is characterized by many necrotic and regenerative muscle fibers without or with minimal inflammatory cell infiltration. The clinical spectrum associated with anti-SRP antibodies seems to be broad. OBJECTIVE: To describe the clinical characteristics, autoantibodies status, and neurological outcome associated with anti-SRP antibody. METHODS: We studied clinical and laboratory findings of 100 patients with inflammatory myopathy and anti-SRP antibodies. Anti-SRP antibodies in serum were detected by the presence of 7S RNA using RNA immunoprecipitation. In addition, enzyme-linked immunosorbent assays (ELISAs) using a 54-kD protein of SRP (SRP54) and 3-hydroxyl-3-methylglutatyl-coenzyme A reductase (HMGCR) were also conducted. RESULTS: The mean onset age of the 61 female and 39 male patients was 51 years (range 4–82 years); duration ≥ 12 months before diagnosis was seen in 23 cases. All patients presented limbs weakness; 63 had severe weakness, 70 neck weakness, 41 dysphagia, and 66 muscle atrophy. Extramuscular symptoms and associated disorders were infrequent. Creatine kinase levels were mostly more than 1000 IU/L. Histological diagnosis showed 84 patients had necrotizing myopathy, and apparent cell infiltration was observed in 16 patients. Anti-SRP54 antibodies were undetectable in 18 serum samples with autoantibodies to 7S RNA. Anti-HMGCR antibodies were positive in 3 patients without the statin treatment, however, were negative in 5 patients with statin-exposure at disease onset. All but 3 patients were treated by corticosteroids and 62 (77 %) of these 81 patients required additional immunotherapy. After 2-years treatment, 22 (27 %) of these 81 patients had poor neurological outcomes with modified Rankin scale scores of 3–5. Multivariate analysis revealed that pediatric disease onset was associated with the poor outcomes. CONCLUSION: Anti-SRP antibodies are associated with different clinical courses and histological presentations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13023-015-0277-y) contains supplementary material, which is available to authorized users.